Criticism Of The Dropship Technique: (Islamic Economic Perspective) - Mukhlas, Abdulloh Arif (Journal of Social Science and Economics, 2022)
Dropship, a business model with no capital, no booth, no employees, no time limit techniques, provides an exciting picture of the future. It is enough to offer other people's merchandise, via cellphone, done while completing other activities, anytime and anywhere. This dropship technique provides many advantages, thus attracting many people. As a religion that comes with perfect rules, how does Islam view these business techniques. Businesses that use this online network, of course, cannot hand over goods directly. Even in this business technique, the goods offered are often owned by someone else. But in reality this business technique is still in axis. This shows that there is an element of mutual voluntary cooperation between the two parties who make transactions. On the one hand, there is the potential for fraud, which is prohibited by Islamic teachings, but on the other hand, there is an element of mutual volunteerism which is the basis of an agreement or contract which is recommended in Islamic teachings as well. From there, there are criticisms that need attention to get improvements, so that it is not only the result that is the goal, but the process also needs to be considered.